Universitetų raidos tendencijos: vadybos ir COVID pandemijos. - Dagys, Jonas (Problems / Problemos, 2020)
The most urgent challenge of this year - the COVID-19 pandemic and measures of response to it - has sharpened and accelerated the process which was initially driven by bureaucratization and formalization: increasing depersonalization of academic life and the erosion of the university as a unique form of coexistence. The Assuming the concept of the university as a value category, this article aims to review and assess the changes in the self-perception of the academic community that have matured and acquired institutional forms in an attempt to adapt to rapidly shifting societal expectations and needs. Modern trends in university development are best expressed in terms such as "bureaucratization", "formalization", "depersonalization", "instrumentalization of knowledge", and "community fragmentation". The pandemic of effective management that has affected Western universities and has gradually reached Vilnius University, no less than the pandemic of COVID-19 and administrative response to it, weakens the academic community based on autonomous and collegial decisions, which should be considered among the most important grounds of uniqueness of university as an institution.